Review of Progress in Quantitative Nondestructive Evaluation 1997
DOI: 10.1007/978-1-4615-5947-4_24
|View full text |Cite
|
Sign up to set email alerts
|

Disperse: A General Purpose Program for Creating Dispersion Curves

Abstract: Mechanical Engineering Oepartment Exhibition Road, London SW7 2BX INTROOUCTIONThe application of guided waves in NOT can be hampered by the Iack of readily available dispersion curves for complex structures. To overcome this hindrance, we have developed a general purpose program that can create dispersion curves for a very wide range of systems and then effectively communicate the information contained within those curves. The program uses the global matrix method to handle multi-layered Cartesian and cylindri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
305
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(312 citation statements)
references
References 10 publications
7
305
0
Order By: Relevance
“…We observed the two waveforms at almost the same time. The measured propagation velocity of both the waves was 1.75 × 10 3 m/s and corresponded to the calculated group velocity of the L(0,1) mode of a guided wave at a frequency of 100 kHz for the used pipe; the group velocity was calculated using the software DISPERSE (6) . H. Sato et al (7) reported the propagation of a guided wave both in the water inside a pipe and in the pipe wall with the same propagation velocity.…”
Section: Pzt Fibersmentioning
confidence: 85%
“…We observed the two waveforms at almost the same time. The measured propagation velocity of both the waves was 1.75 × 10 3 m/s and corresponded to the calculated group velocity of the L(0,1) mode of a guided wave at a frequency of 100 kHz for the used pipe; the group velocity was calculated using the software DISPERSE (6) . H. Sato et al (7) reported the propagation of a guided wave both in the water inside a pipe and in the pipe wall with the same propagation velocity.…”
Section: Pzt Fibersmentioning
confidence: 85%
“…In order to determine window size, the software package DISPERSE v2.0.16i [16] was used to calculate theoretical wavenumber for a number of ply "stackups" corresponding to laminate regions above delaminations at the 4-5, 6-7, 7-8, 17-18 ply interfaces and for the pristine 26 ply plate. Material properties used to perform the calculations are obtained from the literature and are presented in Table 1 [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…3.12, dispersion curves of phase velocity and group velocity are represented against the frequency for symmetric and antisymmetric modes of a 3-mm thick aluminium plate. (Pavlakovic et al 1997) The dispersion equations of Lamb waves for plate-like isotropic structures are (Rose 2014): tan .qh/ q C 4k 2 p tan .ph/ .k 2 q 2 / 2 D 0 for symmetric modes (3.5a) q tan .qh/ C k 2 q 2 2 tan .ph/ 4k 2 p D 0 for antisymmetric modes (3.5b)…”
Section: Dispersion Curvesmentioning
confidence: 99%